An initial and boundary value electromagnetic problem for plasma sphere - Remayeva, Т. (ХНУРЕ, 2012)
The exact expressions for the transformed field caused by a plasma sphere after its instant formation are obtained as a solution of an initial and boundary value electromagnetic problem for the Maxwell’s equations based on the longitudinal and the transverse spherical vector functions.
Keywords: plasma sphere; electromagnetic; Q-factor